KINERJA KEUANGAN BADAN USAHA MILIK DESA - Fitri, Nurul; Septiani, Indri; Nurmiati, Nurmiati (Universitas Patria Artha, 2025)
This study aims to determine and analyze the financial performance of Village-Owned Enterprises (BUMDes) in Kaburu Village, Bontomanai District, Selayar Islands Regency for 2020-2022, based on aspects of financial ratios consisting of Liquidity Ratio, Profitability Ratio, Solvency Ratio and Activity Ratio. This research uses a descriptive method with a quantitative approach with analysis techniques using financial ratio calculation analysis. In this study the data used is the financial statements of the Village-Owned Enterprises (BUMDes) Bukit Harapan Kaburu Village for three periods from 2020 to 2022. The results of the study indicate that in general the financial performance of the Village-Owned Enterprise (BUMDes)